Audit Manajeman Keamanan Informasi Untuk Kelayakan Keamanan Sistem Informasi(Studi Kasus : Politeknik Lamandau, Kalimantan Tengah) - Hidayat, Rahmat; Febriani, Ariana; Nilam Sari, Kurnia Ayu; Rahayu, Riska Puji; Puji Rahayu, Riska (Applied Information Technology and Computer Science (AICOMS), 2023)
It should be written in one paragraph consisting of a maximum of 200 words. For scientific articles, the abstract should provide an overview of the work. We strongly advise authors to use the following structured abstract style, but without headings: (1) Background: Place the question in a broad context and highlight the purpose of the study; (2) Methods: briefly describe the main methods or treatments applied; (3) Results: summarise the main findings of the article; (4) Conclusions: indicate the main conclusions or interpretations. The abstract should be an objective representation of the article and should not contain results that are not presented and substantiated in the main text and should not overstate the main conclusions.